Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

A Quantitative Approach to SIV Functional Latency in Brain Macrophages - Celina Abreu; Erin N. Shirk; Suzanne E. Queen; Joseph L. Mankowski; Lucio Gama; Janice E. Clements (Journal of Neuroimmune Pharmacology, 2019)

CCR2 on Peripheral Blood CD14+CD16+ Monocytes Correlates with Neuronal Damage, HIV-Associated Neurocognitive Disorders, and Peripheral HIV DNA: reseeding of CNS reservoirs? - Mike Veenstra; Desiree A. Byrd; Matilde Inglese; Korhan Buyukturkoglu; Dionna W. Williams; Lazar Fleysher; Ming Li; Lucio Gama; Rosiris León-Rivera; Tina M. Calderon; Janice E. Clements; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2019)

An SIV/macaque model targeted to study HIV-associated neurocognitive disorders - Sarah E. Beck; Suzanne E. Queen; Kelly A. Metcalf Pate; Lisa M. Mangus; Celina M. Abreu; Lucio Gama; Kenneth W. Witwer; Robert J. Adams; M. Christine Zink; Janice E. Clements; Joseph L. Mankowski (Journal of NeuroVirology, 2018)

Genetic and genomic evidence of niche partitioning and adaptive radiation in mountain pine beetle fungal symbionts - Dario I. Ojeda Alayon; Clement K. M. Tsui; Nicolas Feau; Arnaud Capron; Braham Dhillon; Yiyuan Zhang; Sepideh Massoumi Alamouti; Celia K. Boone; Allan L. Carroll; Janice E. K. Cooke; Amanda D. Roe; Felix A. H. Sperling; et al. (Molecular Ecology, 2017)
Bark beetles form multipartite symbiotic associations with blue stain fungi (Ophiostomatales, Ascomycota). These fungal symbionts play an important role during the beetle's life cycle by providing nutritional supplementation, overcoming tree defences and modifying host tissues to favour brood development. The maintenance of stable multipartite symbioses with seemingly less competitive symbionts in similar habitats is of fundamental interest to ecology and evolution. We tested the hypothesis that the coexistence of three fungal species associated with the mountain pine beetle is the result of niche partitioning and adaptive radiation using SNP genotyping coupled with genotype–environment association analysis and phenotypic characterization of growth rate under different temperatures. We found that genetic variation and population structure within each species is best explained by distinct spatial and environmental variables. We observed both common (temperature seasonality and the host species) and distinct (drought, cold stress, precipitation) environmental and spatial factors that shaped the genomes of these fungi resulting in contrasting outcomes. Phenotypic intraspecific variations in Grosmannia clavigera and Leptographium longiclavatum , together with high heritability, suggest potential for adaptive selection in these species. By contrast, Ophiostoma montium displayed narrower intraspecific variation but greater tolerance to extreme high temperatures. Our study highlights unique phenotypic and genotypic characteristics in these symbionts that are consistent with our hypothesis. By maintaining this multipartite relationship, the bark beetles have a greater likelihood of obtaining the benefits afforded by the fungi and reduce the risk of being left aposymbiotic. Complementarity among species could facilitate colonization of new habitats and survival under adverse conditions.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

SIV/Macaque Model of HIV Infection in Cocaine Users: Minimal Effects of Cocaine on Behavior, Virus Replication, and CNS Inflammation - Michael Weed; Robert J. Adams; Robert D. Hienz; Kelly A. Meulendyke; Michael E. Linde; Janice E. Clements; Joseph L. Mankowski; M. Christine Zink (Journal of Neuroimmune Pharmacology, 2012)

Population structure and migration pattern of a conifer pathogen, Grosmannia clavigera , as influenced by its symbiont, the mountain pine beetle - CLEMENT K. M. TSUI; AMANDA D. ROE; YOUSRY A. EL‐KASSABY; ADRIANNE V. RICE; SEPIDEH M. ALAMOUTI; FELIX A. H. SPERLING; JANICE E. K. COOKE; JÖRG BOHLMANN; RICHARD C. HAMELIN (Molecular Ecology, 2012)
We investigated the population structure of Grosmannia clavigera (Gc), a fungal symbiont of the mountain pine beetle (MPB) that plays a crucial role in the establishment and reproductive success of this pathogen. This insect–fungal complex has destroyed over 16 million ha of lodgepole pine forests in Canada, the largest MPB epidemic in recorded history. During this current epidemic, MPB has expanded its range beyond historically recorded boundaries, both northward and eastward, and has now reached the jack pine of Alberta, potentially threatening the Canadian boreal forest. To better understand the dynamics between the beetle and its fungal symbiont, we sampled 19 populations in western North America and genotyped individuals from these populations with eight microsatellite markers. The fungus displayed high haplotype diversity, with over 250 unique haplotypes observed in 335 single spore isolates. Linkage equilibria in 13 of the 19 populations suggested that the fungus reproduces sexually. Bayesian clustering and distance analyses identified four genetic clusters that corresponded to four major geographical regions, which suggested that the epidemic arose from multiple geographical sources. A genetic cluster north of the Rocky Mountains, where the MPB has recently become established, experienced a population bottleneck, probably as a result of the recent range expansion. The two genetic clusters located north and west of the Rocky Mountains contained many fungal isolates admixed from all populations, possibly due to the massive movement of MPB during the epidemic. The general agreement in north–south differentiation of MPB and G. clavigera populations points to the fungal pathogen’s dependence on the movement of its insect vector. In addition, the patterns of diversity and the individual assignment tests of the fungal associate suggest that migration across the Rocky Mountains occurred via a northeastern corridor, in accordance with meteorological patterns and observation of MPB movement data. Our results highlight the potential of this pathogen for both expansion and sexual reproduction, and also identify some possible barriers to gene flow. Understanding the ecological and evolutionary dynamics of this fungus–beetle association is important for the modelling and prediction of MPB epidemics.

Initiation of HAART during acute simian immunodeficiency virus infection rapidly controls virus replication in the CNS by enhancing immune activity and preserving protective immune responses - David R. Graham; Lucio Gama; Suzanne E. Queen; Ming Li; Angela K. Brice; Kathleen M. Kelly; Joseph L. Mankowski; Janice E. Clements; M. Christine Zink (Journal of NeuroVirology, 2011)

Opendra “Bill” Narayan (1936–2007): A Personal Tribute to a Friend, Teacher, and Colleague - Shilpa Buch; Barry T. Rouse; Howard E. Gendelman; M. Christine Zink; Janice E. Clements (Journal of Neuroimmune Pharmacology, 2008)

The accelerated simian immunodeficiency virus macaque model of human immunodeficiency virus–associated neurological disease: From mechanism to treatment - Janice E Clements; Joseph L Mankowski; Lucio Gama; M Christine Zink (Journal of NeuroVirology, 2008)

Second assessment of NeuroAIDS in Africa - Kevin Robertson; Kathy Kopnisky; James Hakim; Concepta Merry; Noeline Nakasujja; Colin Hall; Moussa Traore; Ned Sacktor; David Clifford; Charles Newton; Annelies Van Rie; Penny Holding; et al. (Journal of NeuroVirology, 2008)

Sequence variation in the CC-chemokine ligand 2 promoter of pigtailed macaques is not associated with the incidence or severity of neuropathology in a simian immunodeficiency virus model of human immunodeficiency virus central nervous system disease - Edward K Wright; Janice E Clements; Sheila A. Barber (Journal of NeuroVirology, 2006)

The central nervous system is a viral reservoir in simian immunodeficiency virus–infected macaques on combined antiretroviral therapy: A model for human immunodeficiency virus patients on highly active antiretroviral theraby - Janice E Clements; Ming Li; Lucio Gama; Brandon Bullock; Lucy M Carruth; Joseph L Mankowski; M Christine Zink (Journal of NeuroVirology, 2005)

Innate immune responses and control of acute simian immunodeficiency virus replication in the central nervous system - Sheila A Barber; David S Herbst; Brandon T Bullock; Lucio Gama; Janice E Clements (Journal of NeuroVirology, 2004)

Central Nervous System Correlates of Behavioral Deficits Following Simian Immunodeficiency Virus Infection - Michael R Weed; Robert D Hienz; Joseph V Brady; Robert J Adams; Joseph L Mankowski; Janice E Clements; M Christine Zink (Journal of NeuroVirology, 2003)